Generative AI and Access to Justice in Canada: The Case of Self-Represented Litigants [SRLs] - Ogunde, Fife (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2024)
This article examines generative AI’s influence from the perspective of SRLs, exploring the potential and limitations of Large Language Model [LLM] usage by this category of litigants. The paper argues that LLMs can play a significant role in enabling SRLs present decent cases in court and effectively participate in legal proceedings. However, the inherent deficiencies in LLMs may mean that LLMs do more harm than good to the cause of SRLs, particularly those who lack any form of legal training or knowledge. Ultimately, the ability of SRLs to properly harness the potential of LLMs will depend more on the literacy and understanding of SRLs rather than the availability of the technology.